Peternak Sapi Dan Jebakan Kemiskinan - Yanto Kambaru Njuka Tehik; Adrianus Kabubu Hudang (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2016)
Beef demanding increasing locally and nationally, it was caused by the higher society comsuption. Beef demanding continues to increase the economics. It should be abble to lift the cattle farming households.. However, the actors in this case the small scale economic don’t get the rewards about what they did. These condition take an impact on people who lives as cattle breeders. In addition cattle farmer mired in poverty. To achieve this farmers poverty depedency on the owner capital and merchants this dependence could make the owner capital and traders in bargaining position. Thereefore, the objective of the study were to find out and to describe how the mechanism, dynamic beween cattle breeders and traders and investor relathionship. Who strived in the livestock of sub sector capital, thereby this researc could answer the divestion of why the livestock sektor was not able to improve the domestic economy of cattle farmers in east sumba.This study was conducted in east Sumba. The qualitative method was used in this study. This study showed that cattle ranchers have low education, having 10 years experience in working 75% percent of cattle respondents using family labor, 70 % cattle respondents source comes from the own cattle. In addition, cattle ranches sell their animals when it was urgent for example in this case it cause position bargaining becomes the farmer weak and vulnerable trapped in poverty. In conclusion cattle breeders made this job as side business.Kata Kunci: Peternak Sapi, Pemilik Modal, Jebakan Kemiskinan dan Eksploitasi